Does combiotic administration at artificial insemination improve fertility? - Davis, Duane L.; Scmidt, W.E.; Stevenson, Jeffrey S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Injecting gilts with 10 cc’s combiotic at artificial insemination did not improve farrowing rate or litter size.
Keywords: Swine; Artificial insemination; Fertility